1997
DOI: 10.1007/bf01231468
|View full text |Cite
|
Sign up to set email alerts
|

Staggered contracts and profitable entry deterrence: an application to professional sports

Abstract: long-term contracts, entry deterrence, professional sports, JEL classification, L14, J23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The cost of replacements (transfer fees, wages and search costs) would be too great to bear. Thus, staggered contracts reduce the hold‐up risks that clubs are confronted with (Frascatore, ). It is notable that Frick's study pre‐dates the growth of rolling, conditional contracts that we now observe in European football leagues.…”
Section: Shirking In Sportsmentioning
confidence: 99%
“…The cost of replacements (transfer fees, wages and search costs) would be too great to bear. Thus, staggered contracts reduce the hold‐up risks that clubs are confronted with (Frascatore, ). It is notable that Frick's study pre‐dates the growth of rolling, conditional contracts that we now observe in European football leagues.…”
Section: Shirking In Sportsmentioning
confidence: 99%
“…The study concluded that moral hazard is a widespread phenomenon, even in professional football, and that player wage differences can be explained to a large extent by differences in individual performance, with differences in player performance significantly reduced in the final year of the contract. Mark R. Frascatore [4]analyzes and proves that the strategy of offering amazing long-term contracts to star players can reduce the wage bill of existing leagues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To overcome the hold-up problem, a number of solutions has been proposed in the literature, including, among others, the assignment of property rights and changes in the structure of governance to allow for the incentives of the partners involved in a transaction to be aligned (Grossman and Hart 1986, Aghion and Tirole 1997, Frascatore 1997. Alternatively, Aghion et al (1994) or Wait (2005) suggest a contract design that can guide the ex-post renegotiation process, while Felli and Roberts (2015) and MacLeod and Malcomson (1993) discuss improving market contracts, and Baker et al (2002) emphasize the value of future relationships (relational contracts).…”
Section: Literaturementioning
confidence: 99%